Clinical Progression and Load Management For Proximal Hamstring Tendinopathy In A Long-Distance Runner: A Case Report - Cristina Campos-Villegas; Lucía Ortega-Pérez de Villar; Javier Gámez-Payá; Jorge Alarcón-Jiménez; Nieves de Bernardo (International Journal of Sports Physical Therapy)
# Background and Purpose